2016
DOI: 10.1136/inp.i1849
|View full text |Cite
|
Sign up to set email alerts
|

Common ECG abnormalities in the perioperative period

Abstract: Electrocardiography is a useful tool for monitoring all patients during the perioperative period to determine heart rate, the presence of arrhythmias and conduction defects. It may be argued that routine monitoring of an electrocardiogram (ECG) of a healthy patient is unnecessary; however, unexpected, more malignant arrhythmias – some of which can be life threatening – may be present and would remain undiagnosed and therefore untreated if the ECG was not monitored. This article describes how to interpret abnor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…The most common findings of hyperkalaemia under anaesthesia are due to changes in cell membrane excitability and include arrhythmias (bradycardia, altered ECG morphology (flattened P waves, narrow T waves of increased amplitude, prolonged QRS complex)) due to prolonged depolarisation and repolarisation of the myocardium, 22 slowing the rate of cardiac pacemaker discharge. 23 Early experimental studies inducing hyperkalaemia in horses found ECG changes to be progressive according to the degree of hyperkalaemia and speed of potassium administration, with rapid administration having more marked effects on the ECG. 24,25 Although P wave changes occurred with plasma concentrations over 6.2mmol/L, asystole did not occur until plasma potassium was over 9.4 mmol/L.…”
Section: Hyperkalaemiamentioning
confidence: 99%
“…The most common findings of hyperkalaemia under anaesthesia are due to changes in cell membrane excitability and include arrhythmias (bradycardia, altered ECG morphology (flattened P waves, narrow T waves of increased amplitude, prolonged QRS complex)) due to prolonged depolarisation and repolarisation of the myocardium, 22 slowing the rate of cardiac pacemaker discharge. 23 Early experimental studies inducing hyperkalaemia in horses found ECG changes to be progressive according to the degree of hyperkalaemia and speed of potassium administration, with rapid administration having more marked effects on the ECG. 24,25 Although P wave changes occurred with plasma concentrations over 6.2mmol/L, asystole did not occur until plasma potassium was over 9.4 mmol/L.…”
Section: Hyperkalaemiamentioning
confidence: 99%